2023
DOI: 10.1038/s41598-023-44468-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil bacteria on habitat-specialization and abundance gradient to different afforestation types

Zhenlu Qiu,
Jie Li,
Peng Wang
et al.

Abstract: Studies involving response of subgroups of soil microorganisms to forest change, especially comparative studies on habitat-specialization and abundance gradient were still lack. In this study, we analyzed the response of soil bacterial diversity and structure to afforestation types and its relationship to environment of Fanggan ecological restoration area under the classification of subgroups by habitat-specialization and abundance gradient based on abundance ratio respectively. The results were: (1) On the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Deserts, while being potentially large CO 2 sinks, face challenges as rising soil temperatures can cause soil air expansion and increased CO 2 release into the atmosphere under climate change circumstances [51]. A recent study has revealed differences in microbial community and biodiversity among soil environments [49,50,[52][53][54][55][56]. The decline in soil microbial diversity also poses a significant danger to the ecosystem balance.…”
Section: Introductionmentioning
confidence: 99%
“…Deserts, while being potentially large CO 2 sinks, face challenges as rising soil temperatures can cause soil air expansion and increased CO 2 release into the atmosphere under climate change circumstances [51]. A recent study has revealed differences in microbial community and biodiversity among soil environments [49,50,[52][53][54][55][56]. The decline in soil microbial diversity also poses a significant danger to the ecosystem balance.…”
Section: Introductionmentioning
confidence: 99%